Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.

Plans Are Worthless but Planning Is Everything: A Theoretical Explanation of Eisenhower’s Observation - Garcia Contreras, Angel F.; Ceberio, Martine; Kreinovich, Vladik (Decision Making under Constraints, 2020)
The 1953–1961 US President Dwight D. Eisenhower emphasized that his experience as the Supreme Commander of the Allied Expeditionary Forces in Europe during the Second World War taught him that “plans are worthless, but planning is everything”. This sound contradictory: if plans are worthless, why bother with planning at all? In this paper, we show that Eisenhower’s observation has a meaning: while directly following the original plan in constantly changing circumstances is often not a good idea, the existence of a pre-computed original plan enables us to produce an almost-optimal strategy—a strategy that would have been computationally difficult to produce on a short notice without the pre-existing plan.